2019
DOI: 10.1182/blood-2019-126723
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Cytarabine Is Indispensable for the Survival of Children with Myeloid Leukemia of Down Syndrome Despite Negative Minimal Residual Disease Post-Induction

Abstract: Introduction. Myeloid leukemia in children with Down syndrome (ML-DS) is a unique subtype of acute myeloid leukemia, distinguished by an earlier age of onset (under 4 years of age); somatic mutations of GATA1; hypersensitivity of leukemic blasts to cytarabine and other chemotherapeutic agents; lack of CNS involvement; and superior event-free survival (EFS, 85-90% at 5 years). Due to these excellent outcomes, successive protocols by the Children's Oncology Group (COG) have aimed for a reduction of treatment int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Complex karyotypes have been reported to be associated with an unfavorable therapy outcome in adult and childhood malignant myeloid disorders [66][67][68]. Worse outcomes related to CK were previously observed in DS-AML [23,41], although another group could not associate CK with worse OS, EFS or CIR [57]. In this report, CK, as well as non-megakaryoblastic immunophenotype and older age, were identified as poor prognostic factors.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Complex karyotypes have been reported to be associated with an unfavorable therapy outcome in adult and childhood malignant myeloid disorders [66][67][68]. Worse outcomes related to CK were previously observed in DS-AML [23,41], although another group could not associate CK with worse OS, EFS or CIR [57]. In this report, CK, as well as non-megakaryoblastic immunophenotype and older age, were identified as poor prognostic factors.…”
Section: Discussionsupporting
confidence: 48%
“…Also, only one patient of sporadic DS-AML aged 11 years old presented a favorable cytogenetic rearrangement [6,33,37,58,60]. As previously described, the incidence of chromosomal abnormalities was higher in AML than in TAM patients [22,61], being +8 the most frequent chromosome alteration = [30,[33][34][35]37,41,57,59,60].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Due to concerns regarding increased treatment-related toxicity in children with ML–DS [ 28 30 ], sequential protocols successfully reduced cumulative exposure to several agents including daunorubicin, etoposide, and intrathecal cytarabine without impacting on overall outcome [ 13 , 14 , 26 , 27 ]. High-dose cytarabine was established as an important component of therapy, with early administration leading to improved outcomes [ 13 ] and subsequent attempts to omit high-dose cytarabine in standard-risk patients resulting in significantly lower event-free survival [ 31 ]. Several studies have identified older age as an unfavorable independent prognostic feature [ 26 , 27 , 32 ].…”
Section: Clinical Features Therapy and Outcome Of Ds-associated Leumentioning
confidence: 99%
“…Instead, intensification included two cycles of cytarabine and etoposide. Currently, the first prospective trial based on risk stratification in this patient group is being conducted through an assessment of MRD levels at the end of induction I [ 45 ].…”
Section: Specific Subgroupsmentioning
confidence: 99%